2007
DOI: 10.3390/s7060797
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development in Optical Fiber Biosensors

Abstract: Remarkable developments can be seen in the field of optical fibre biosensors in the last decade. More sensors for specific analytes have been reported, novel sensing chemistries or transduction principles have been introduced, and applications in various analytical fields have been realised. This review consists of papers mainly reported in the last decade and presents about applications of optical fiber biosensors. Discussions on the trends in optical fiber biosensor applications in real samples are enumerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
137
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(141 citation statements)
references
References 244 publications
0
137
0
4
Order By: Relevance
“…Basic principles and common geometries of tapered fiber-optic biosensors were reviewed by Leung et al (2007) and detailed account of their use for detection of biomolecules was presented. Bosch et al (2007) also presented an exhaustive review of fiber optic biosensors in terms of detection phenomena used viz. absorbance, reflectance and fluorescence measurement and details of applications of fiber optic biosensors.…”
Section: Classification Of Fiber Optic Biosensorsmentioning
confidence: 99%
“…Basic principles and common geometries of tapered fiber-optic biosensors were reviewed by Leung et al (2007) and detailed account of their use for detection of biomolecules was presented. Bosch et al (2007) also presented an exhaustive review of fiber optic biosensors in terms of detection phenomena used viz. absorbance, reflectance and fluorescence measurement and details of applications of fiber optic biosensors.…”
Section: Classification Of Fiber Optic Biosensorsmentioning
confidence: 99%
“…(a) Top view of the optical fiber probe: photonic integrated circuit aligned to the core of the optical fiber. The circuit is designed so that light is coupled in and out via the same grating coupler [7] and it is also required to be compact in order to fit on the facet of a standard single-mode optical fiber. A focused grating coupler is used to circumvent the need for a space consuming waveguide taper [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, many applications require a sensor probe that is flexible, portable, and can perform measurements at locations that are hard to reach [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Further on, Phillips [57] demonstrated that ide− ally glassy materials have hydrogen−bonded networks. Bosch et al [58] in 2007 critically reviewed the last decade developments in optical fibres for bio sensing. In the same year Vassilev et al [59] introduced the new Se−based multi− component chalcogenide glasses and studied their composi− tion dependence on physical properties.…”
Section: Global Status Of Metal Containing Chalcogenide Glassesmentioning
confidence: 99%